Notes on Scaphidium grande-complex with description of a new species from China (Coleoptera: Staphylinidae: Scaphidiinae) - Tang, Liang; Tu, Yue-Ye; Li, Li-Zhen (Zootaxa, 2016)
A new species of the Scaphidium grande- complex, S. yuzhizhoui sp. n., collected from Guangdong Province is described and its diagnostic characters are illustrated. Scaphidium inflexitibiale Tang & Li, 2010 is recorded from Laos for the first time.